2007
DOI: 10.1016/j.tra.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Trails, lanes, or traffic: Valuing bicycle facilities with an adaptive stated preference survey

Abstract: This study evaluates individual preferences for five different cycling environments by trading off a better facility with a higher travel time against a less attractive facility at a lower travel time. The tradeoff of travel time to amenities of a particular facility informs our understanding of the value attached to different attributes such as bike-lanes, off-road trails, or side-street parking. The facilities considered here are off-road facilities, in-traffic facilities with bike-lane and no on-street park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 4 publications
9
174
1
4
Order By: Relevance
“…A relatively large survey of 1,862 cyclists in Queensland, Australia found that women are more likely to cycle off-road than men; are less likely to commute by bicycle than men; and that, although factors related to traffic conditions, motorist aggression and safety are concerns for both women and men, women report a far greater number of these constraints (Heesch, Sahlqvist, and Garrard 2012). Similar findings were identified by Tilahun, Levinson, and Krizek (2007) in a study of participantsÕ stated preferences around route choice. Observational studies have also shown these preferences to be expressed in womenÕs real cycle behaviours.…”
Section: Related Work: Gender and Cycling Behaviourmentioning
confidence: 54%
“…A relatively large survey of 1,862 cyclists in Queensland, Australia found that women are more likely to cycle off-road than men; are less likely to commute by bicycle than men; and that, although factors related to traffic conditions, motorist aggression and safety are concerns for both women and men, women report a far greater number of these constraints (Heesch, Sahlqvist, and Garrard 2012). Similar findings were identified by Tilahun, Levinson, and Krizek (2007) in a study of participantsÕ stated preferences around route choice. Observational studies have also shown these preferences to be expressed in womenÕs real cycle behaviours.…”
Section: Related Work: Gender and Cycling Behaviourmentioning
confidence: 54%
“…Ironically, Berlin owes its bicycle friendly urban form to planning agendas either contrary to, or detached from, cycling promotion. Studies suggest that in the context of low bicycle use (as Berlin had until the 1990s), segregated cycle lanes can nurture increased levels of cycling participation to a significant extent (Wardman et al, 2007;Tilahun et al, 2007). Given an inherited urban form conducive to high cycling rates-wide spacious streets, extensive segregated cycle infrastructure, and prevalent cycling appropriate journey lengths -pre-existing urban form seems to have played a key role.…”
Section: Re-examining Berlin's Cycling Transitionmentioning
confidence: 99%
“…Also, the zones of these models are poorly matched to the spatial scale of movement by these modes, resulting in a considerable number of intrazonal trips (Eash 1999). While vehicular travel tends to be most sensitive to travel times and levels of network congestion, non-motorized route choices tend to include factors that may be more qualitative, experiential or difficult to operationalize, such as facility design and aesthetic treatments that may fall under the broad category of "environmental factors" (Porter et al 1999,Tilahun 2007. That is not to suggest travel time is not an important determinant of route choice for non-motorized travelers (Stinson and Bhat 2003;Weinstein 2007)-just that it is not quite as decisive.…”
Section: Measuring Accessibility For Non-motorized Travelmentioning
confidence: 99%